(untitled) (Journal of Hama University, 2025)
The research was conducted in the Environmental Engineering Laboratory at the Faculty of Civil Engineering Al-Baath University, where the primary objective of the research was to study the efficiency of the Duckweeds plant in reducing the concentrations of phosphorus present in the industrial wastewater resulting from the industrial city of Hassia in Homs Governorate. In order to conduct the research, two basins were designed with two different heights (H1 = 65cm, H2 = 25cm) and two residence times were adopted in them (T1=7,T2=15)day. Surface hydraulic loads were applied at time T1, their values ​​ranging from (0.036 - 0.093 m3/m2.d), and their values ​​at time T2 ranging from (0.016 - 0.043 m3/m2.d), after planting the two beds with plants and taking samples at Values ​​for pH (pH1 = 7.7, pH2 = 4.7). The results of laboratory measurements obtained showed that the phosphorus removal rate was approximately 62.51% at a depth of 25 cm, after a dwell time T = 15 days, and at a hydraulic load of 0.016 m3/m2.d, as it was The efficiency of removing phosphorus from water at pH = 7.7 was higher than water with pH = 4.7. Therefore, the results proved that the water lentil plant has good removal efficiency. It also showed that the water lentil has the ability to live and grow in the temperature range used [12-20]°C. The method of phytoremediation using water lentil plants is an economical method that can be adopted.